The The Effect of Tobacco Cigarette and Electronic Cigarette Exposure on Body Microbiota: A Systematic Review in Animal Models - Nopsa Azzahra Dwi Permatasari; Ismiralda Oke Putranti (Indonesian Journal of Global Health Research, 2025)
Exposure to tobacco and e-cigarette (vape) smoke is a significant factor affecting health, especially regarding the composition and balance of the body's microbiota. Objective to evaluate the impact of exposure to both types of cigarette smoke on body microbiota, particularly oral, gut and respiratory microbiota. A literature search was conducted following PRISMA guidelines through the Google Scholar, PubMed, and Research Gate databases for the period 2015-2025. A total of 4,257 articles were identified, and after screening, obtained 7 in vivo experimental studies using the PICO method, focusing on the effects of chronic cigarette smoke exposure on microbiota composition, inflammation, and dysbiosis were selected, all conducted on animal models. The analysis showed that exposure to tobacco and e-cigarette smoke caused microbiota dysbiosis, characterized by decreased diversity of commensal microbes and increased prevalence of pathogenic bacteria, such as Porphyromonas gingivalis in the oral microbiota, Proteobacteria in the gut microbiota, and Streptococcus, Fusobacterium, Prevotella, and Haemophilus in the respiratory tract microbiota. The main mechanisms of microbiota disruption involve oxidative stress and chronic inflammation induced by chemical components in cigarette smoke. Exposure to cigarette smoke, both tobacco and e-cigarette, has a significant impact on the body's microbiota, potentially increasing the risk of inflammatory diseases, metabolic disorders, and respiratory tract infections.